Fibroblast growth factor 23 and Klotho contribute to airway inflammation. Issue 1 (5th July 2018) - Krick, Stefanie; Grabner, Alexander; Baumlin, Nathalie; Yanucil, Christopher; Helton, Scott; Grosche, Astrid; Sailland, Juliette; Geraghty, Patrick; Viera, Liliana; Russell, Derek W.; Wells, J. Michael; Xu, Xin; et al.
Circulating levels of fibroblast growth factor (FGF)23 are associated with systemic inflammation and increased mortality in chronic kidney disease. α-Klotho, a co-receptor for FGF23, is downregulated in chronic obstructive pulmonary disease (COPD). However, whether FGF23 and Klotho-mediated FGF receptor (FGFR) activation delineates a pathophysiological mechanism in COPD remains unclear. We hypothesised that FGF23 can potentiate airway inflammation via Klotho-independent FGFR4 activation. FGF23 and its effect were studied using plasma and transbronchial biopsies from COPD and control patients, and primary human bronchial epithelial cells isolated from COPD patients as well as a murine COPD model. Plasma FGF23 levels were significantly elevated in COPD patients. Exposure of airway epithelial cells to cigarette smoke and FGF23 led to a significant increase in interleukin-1β release via Klotho-independent FGFR4-mediated activation of phospholipase Cγ/nuclear factor of activated T-cells signalling. In addition, Klotho knockout mice developed COPD and showed airway inflammation and elevated FGFR4 expression in their lungs, whereas overexpression of Klotho led to an attenuation of airway inflammation. Cigarette smoke induces airway inflammation by downregulation of Klotho and activation of FGFR4 in the airway epithelium in COPD. Inhibition of FGF23 or FGFR4 might serve as a novel anti-inflammatory strategy in COPD. Fibroblast growth factor 23 and cigarette smoke-induced FGFR4 signalling lead to the development of airway inflammation and emphysema http://ow.ly/j4tZ30jWyGF